Rehabilitation following anterior acromioplasty [Anterior akromiyoplasti sonrasi rehabilitasyon.] - (:unkn) unknown (My University, 2003)
The shoulder region is one of the most challenging part of the human body to rehabilitate. Postoperative days following anterior acromioplasty are painful, with a high potential course of developing soft tissue fibrosis and joint contracture. In the past, following anterior acromioplasty and/or rotator cuff repair, the rehabilitation process was usually delayed for up to four to six weeks to allow healing of the repaired site. This conservative rehabilitation approach resulted in significant restrictions in glenohumeral and scapular joint mobility, weakness of the shoulder girdle musculature, prolonged pain, and functional limitations. Currently the trend of rehabilitation following anterior acromioplasty shifted toward a more earlier and aggressive approach thanks to improved surgical and soft tissue fixation techniques and advances in arthroscopic procedures. This has allowed active-assisted shoulder motion immediately after subacromial decompression and rotator cuff surgery. The rehabilitation team following anterior acromioplasty of the shoulder should consist of the physiatrist, orthopedic surgeon, physical therapist, and the patient.